2023
DOI: 10.1002/jgc4.1711
|View full text |Cite
|
Sign up to set email alerts
|

Genetic counselors' perceptions of student supervision across service delivery models

Abstract: Genetic counseling (GC) services are increasingly delivered by phone or video, resulting in more telehealth student rotations. The purpose of this study was to describe genetic counselors' utilization of telehealth for student supervision and to compare how their comfort, preferences, and perception of the difficulty of selected student supervision competencies vary between phone, video, and in‐person student supervision. In 2021, patient‐facing genetic counselors in North America with ≥1‐year GC experience wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…Similar to findings from Lichten et al. (2023), participants noted that the dynamics of their supervisory interactions with students during the counseling session were affected as well, leading to more independence from students. It was not as easy for students to provide non‐verbal cues to their supervisors when they were unsure how to proceed, and so they were more often challenged to proceed with more difficult discussions.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Similar to findings from Lichten et al. (2023), participants noted that the dynamics of their supervisory interactions with students during the counseling session were affected as well, leading to more independence from students. It was not as easy for students to provide non‐verbal cues to their supervisors when they were unsure how to proceed, and so they were more often challenged to proceed with more difficult discussions.…”
Section: Discussionsupporting
confidence: 77%
“…A recent study by Lichten et al. (2023) demonstrated that genetic counseling supervisors were less comfortable supervising students via remote rotations (particularly through telephone rotations) than though in‐person appointments. Consistent with our study, Lichten's findings indicated that the student/supervisor relationship may be different via telehealth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation